A two-year sonographic follow-up after intratendinous injection therapy in patients with tennis elbow. Issue 8 (29th July 2008) - Zeisig, E; Fahlström, M; Öhberg, L; Alfredson, H
Abstract : Background: Tennis elbow is a tendinopathy affecting the upper extremity. Recent studies have shown high sensitivity for ultrasound (US) examination and high specificity for colour Doppler (CD) examination. There are no mid- or long-term follow-up investigations of the tendon structure and blood flow using these techniques. Objective: To use US and CD to study structure and blood flow in the extensor origin in patients with tennis elbow treated with intratendinous injections. Design: Follow-up study Setting: Sports Medicine Unit, Umeå University. Patients: 25 patients (28 elbows), mean age 46 years (range 27–66), treated with intratendinous injections due to chronic pain from tennis elbow. Method: US and CD examination of the extensor origin was carried out at inclusion and at follow-up two years after intratendinous injection treatment with polidocanol and/or a local anaesthetic. Main outcome measurements: US (structure) and CD (blood flow) findings. Results: All patients had structural tendon changes and high blood flow at inclusion when given the injection treatment. At the two-year follow-up, structural tendon changes were seen in 20/28 elbows and high blood flow was seen in 4/28 elbows. The majority of patients with a good clinical result after treatment had no visible blood flow (17/20), but the structural changes showed no relation to a good result (13/20 remaining changes). Conclusions: Doppler findings, but not structure, might be related to the clinical result after intratendinous injection treatment of tennis elbow.